P–308 Fertility preservation in endometriosis: Appraising the factors affecting the ovarian response. (6th August 2021) - Goaz, S; Fouks, Y; Azem, F
Abstract: Study question: To estimate the factors affecting the ovarian response in women with endometriosis who seek fertility preservation. Summary answer: AMH was the most important predictor of ovarian response. What is known already: Endometriosis is a chronic disease characterised by the presence of endometrial tissue outside the uterine mucosa. This condition affects up to 10% of reproductive-aged women and up to 50% of women with infertility. Infertility in patients affected with endometriosis has been thought to stem mainly from the inherent effect of implants on the ovarian reserve or by the distortion of the female upper reproductive tract organs in the late stages of the disease. Women diagnosed with endometriosis should be counselled about family planning however, the data available to guide these patients regarding fertility preservation or oocyte freezing is scarce. Study design, size, duration: A Retrospective cross-sectional study was conducted from July 2017 to May 2020 at a university-affiliated medical center. Patients who had been treated in the endometriosis clinic and underwent controlled ovarian stimulation and oocyte retrieval for fertility preservation, filled an online questionnaire crossed reference with electronic chart analysis related to patient data and fertility preservation cycles. Participants/materials, setting, methods: Eighty-one patients were included and categorized into two groups according to the number of oocytes retrieved: 0–5 (Group A, n = 26) low ovarian response and 6 or more oocytes (Group B, n = 55). Main results and the role of chance: The severity and duration of the disease so as the symptoms indicative of deep infiltrating endometriosis, were not associated with reduced numbers of vitrified oocytes. The presence of deep infiltrating implants was not associated with numbers of vitrified oocytes (44.4% vs 70.6%, p = 0.08). More Patients who underwent surgical interventions, had significantly lower ovarian responses compared to women who had no intervention (95.2% vs 61.5%, respectively, p = 0.005). A multivariate logistic regression adjusted for the number of oocyte vitrified revealed that anti-Müllerian hormone (AMH) level below 0.8 ng/ml was the only factor significantly associated with low ovarian response, with an adjusted odds ratio of 13.40 (2.02–157.27, p = 0.015). Limitations, reasons for caution: The size of our cohort is relatively small for the number of covariates, reducing the impact of our results when put on an international scope and the lack of information regarding the return rate of patients who had their oocytes vitrified in the attempt of achieving a pregnancy. Wider implications of the findings: We believe that since the practice of FP for endometriosis is relatively new and there is a substantial lack of data, this cohort represents an important contribution to existing literature by extracting data from medical files and cross-referencing them with existing data for fertility specialists, patient encounters, and hospital registries. Trial registration number: Not applicable